2021
DOI: 10.1016/j.jvs.2021.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter global early feasibility study to evaluate total endovascular arch repair using three-vessel inner branch stent-grafts for aneurysms and dissections

Abstract: Objective: We evaluated the outcomes of total endovascular aortic arch repair using three-vessel inner branch stentgrafts for aneurysms and chronic dissections.Methods: We reviewed the clinical data and outcomes of consecutive patients treated by total endovascular aortic arch repair at eight academic centers using three-vessel inner branch stent-grafts (William Cook Europe, Bjaeverskov, Denmark) from 2016 to 2019. All patients received three-vessel designs with two antegrade and one retrograde inner branch, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(15 citation statements)
references
References 33 publications
(53 reference statements)
0
14
0
1
Order By: Relevance
“…The forces and movements on endografts in the ascending aorta and aortic arch are not extensively researched, although it has been suggested they are more pronounced compared with more distal and static portions of the aorta, 10 where these compressions had been seen. 4 These forces may have been accentuated by the tortuous course of the branch owing to the slight misalignment during initial placement and the very fast remodeling evident on the significant shrinkage of the aneurysm in the early follow-up period. The latter, combined with the small diameter of the false lumen and misalignment between the branch and the ostium, may have led to an external compression of the branch by the dissection flap that tends to become less pliable after the first months after an acute dissection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The forces and movements on endografts in the ascending aorta and aortic arch are not extensively researched, although it has been suggested they are more pronounced compared with more distal and static portions of the aorta, 10 where these compressions had been seen. 4 These forces may have been accentuated by the tortuous course of the branch owing to the slight misalignment during initial placement and the very fast remodeling evident on the significant shrinkage of the aneurysm in the early follow-up period. The latter, combined with the small diameter of the false lumen and misalignment between the branch and the ostium, may have led to an external compression of the branch by the dissection flap that tends to become less pliable after the first months after an acute dissection.…”
Section: Discussionmentioning
confidence: 99%
“…This complication seems to be rare, given the good results after the endovascular repair of post type A dissection. 4 However, given its potential consequences, in cases of misalignment and difficulties in catheterizing branches, it may be prudent to liberally reinforce the branches with several high-radial force stents and have a more vigorous follow-up until the remodeling of the aneurysm is verified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported quite low rates of neurological complications after total endovascular arch repair. 17,18 However, the freedom from secondary intervention at 1 year was relatively high (60%-75%), despite being successful. Hence, these TEVAR-related complications should be the focus of future improvements of these less invasive procedures including HAR and total endovascular aortic arch repair.…”
Section: Discussionmentioning
confidence: 99%
“…4 In experienced hands, arch-branched graft technology has proved an alternative to open surgery 3 but it has its problems-not least neck swelling and haematoma as complications of carotid artery cut-down while ACT exceeds 350 second. 5 To mitigate this, we have developed this total percutaneous approach described in incremental steps, with rerouting of the preloaded LSCA/LCCA branch catheter and a modification of the previously described percutaneous axillary artery access technique. 6 The TAT route allows reliable advancement of an 8Fr sheath into the LCCA branch, which provides a stable platform for LCCA catheterization and stenting from femoral access.…”
Section: Bct Bridging Stentmentioning
confidence: 99%